Relasi Agama dan Negara di Indonesia : Tinjauan Historis dan Perkembangan Kontemporer - Anyta Widianti; Amri Tajuddin; Abdullah (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This paper discusses the relationship between religion, especially Islam, and the state in Indonesia, focusing on its historical dynamics since the entry of Islam into the archipelago during the kingdom era to contemporary developments post-Reformasi. The purpose of this study is to understand the relationship between religion (Islam) and the state in Indonesia through historical exploration and various events that shaped the relationship. The method used is qualitative research with a literature study approach that refers to primary and secondary data sources. The primary data sources used include official documents such as the text of Pancasila, the 1945 Constitution, and decisions of the Constitutional Court related to religious issues. Meanwhile, secondary data sources are in the form of books, articles, and research results related to the relationship between religion and the state in Indonesia. The results of the study show that the relationship between religion (Islam) and the Indonesian state cannot be separated, considering that Islam has been the majority religion of the Indonesian population since before independence and has influenced many aspects of the country's life. Islam also plays an important role in the formulation of Pancasila and the 1945 Constitution, which reflect religious values ​​in the state system. In addition, contemporary developments show that Islam continues to influence state policies, such as the formation of sharia regulations, the regulation of religious courts, the implementation of the hajj pilgrimage, sharia banking, halal product certification, and several decisions of the Constitutional Court that reflect the application of Islamic values ​​in national and state life. This study confirms that the relationship between religion (Islam) and the state in Indonesia continues to develop along with the dynamics of social, political, and legal in Indonesia.